Intestinal mal-rotation in an adolescent boy - Shah, Nidhi; Bhimani, Zulekha; Deolekar, S.; Eswar, P. S.; Malik, Mehnish (International Surgery Journal, 2025)
Intestinal malrotation is a developmental anomaly of the midgut in which the normal fetal rotation of intestines around the superior mesenteric artery and their fixation in the peritoneal cavity fail. Rotational anomalies of the midgut are rare in adolescent age. Operative intervention is required generally when they are symptomatic. While difficult to diagnose, prompt recognition and surgical treatment usually lead to a successful outcome. So here we have discussed this rare case of malrotation in adolosance, similar study has been published by Nakajima et al, in-world journal of emergency surgery 2013.